Body Mass Index, Eating Habits and Physical Activity Among Dietetics Students in Universiti Sultan Zainal Abidin - Nurul Syahirah Rusli; Sakinah Harith (Journal of Nutrition Science, 2020)
University life is a critical period of change in eating habits. Weight gain is a serious problem among youths who are experiencing a change in university life. Universities are potentially important settings for promotion of healthy diet and weight management practice for healthy future. Present study aimed to assess physical activity, eating habits and their association with body mass index (BMI) in dietetics students at Universiti Sultan Zainal Abidin (UniSZA). A total of 126 students were involved in answering a set of survey questions as well as weight and height measurements. Data were analyzed using SPSS version 22.0. Result showed that, 9.5% of dietetics students were obese and 25.4% were overweight. Breakfast was the most frequently skipped meal (71.4%) with the main reason of time management followed by busyness in attending lectures and doing readings. Majority of students (73%) will take a snack when they skipped their meal time. Most of the students consume fruits sometimes (55.6%) and 37.3% of them also consume vegetables sometimes. Most of the students (37.3%) consumes fast food one to three times per month. More than half of the students (59.5%) prefer to eat with friends. Majority of students have moderate physical activity (42.9%). However, this study also did not show association between physical activity, eating habits and BMI. In a nutshell, health programs are necessary to create awareness of nutrition and a healthy lifestyle among youth as the arising of obesity incidence among youth is worrying.